Aplasia in Chronic Phase CML Post-TKI Therapy: A Management Dilemma. (22nd September 2019) - Ramdial, Jeremy L.; Aguirre, Luis E.; Ali, Robert A.; Swords, Ronan; Goodman, Mark
Abstract : Transient cytopenias and bone marrow hypoplasia commonly occur during treatment of CML with TKIs (tyrosine kinase inhibitors). This is usually related to the eradication of CML clones that initially compose the majority of hematopoietic cells in the bone marrow at the time of diagnosis. With continuation of effective therapy, normal blood counts return as normal hematopoiesis is restored and CML clones are reduced. Though rare and more unusual than myelodysplastic syndrome (MDS), isolated instances of persistent marrow aplasia have been documented with chronic use of TKIs. We describe two such instances of chronic phase CML where no significant reduction of CML clones was achieved following treatment with TKIs, but bone marrow aplasia occurred resulting in persistent dysfunctional hematopoiesis. Due to prolonged aplasia/hypoplasia, such patients are no longer amenable to TKI treatment. CML progression to accelerated or blast phase in that setting would likely be fatal.